2019
DOI: 10.1002/jcp.29077
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of serotonin nuclei retrieve the lost memory in Alzheimer's disease

Abstract: How are memories stored and retrieved? It was one of the most discussed questions in the past century by neuroscientists. Leading studies of the period brought two different explanations to this question: The first statement considers memory as a physiological change in the brain and suggest that the retrieval of memory is only occurred by the same physiologic changes observed during the memory formation, while the second suggests that memory is a psychic mood stored in mind and the retrieval of memory is occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Optogenetic (Warden et al, 2012 ) or pharmacogenetic (Teissier et al, 2015 ) activation of serotonin neurons in the DRN leads to antidepressant consequences, which is consistent with the effect of acute selective serotonin reuptake inhibitor (SSRI) administration (Kurt et al, 2000 ). In addition to mental disorder, dysfunction of the serotonergic system is also closely related to Alzheimer’s disease (Bostanciklioğlu, 2020 ) and Parkinson’s disease (Fox et al, 2009 ; Polotis and Niccolini, 2015 ). Although drugs that target 5-HT receptors and/or 5-HT transporter work well against the above diseases, side effects such as drug resistance and high recurrence rate are also reported in some studies (Mueller et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Optogenetic (Warden et al, 2012 ) or pharmacogenetic (Teissier et al, 2015 ) activation of serotonin neurons in the DRN leads to antidepressant consequences, which is consistent with the effect of acute selective serotonin reuptake inhibitor (SSRI) administration (Kurt et al, 2000 ). In addition to mental disorder, dysfunction of the serotonergic system is also closely related to Alzheimer’s disease (Bostanciklioğlu, 2020 ) and Parkinson’s disease (Fox et al, 2009 ; Polotis and Niccolini, 2015 ). Although drugs that target 5-HT receptors and/or 5-HT transporter work well against the above diseases, side effects such as drug resistance and high recurrence rate are also reported in some studies (Mueller et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…We could speculate that the reason for increased serotonin level is to stimulate the release of neurotrophic factors triggering neuroplasticity and repairing mechanisms to protect neurons near to death, a destroying and exhausting process. A bulk of evidence indicated that serotonin is a key neuroprotective neurotransmitter 4 and this protective effect is specific for serotonin because other neurotransmitters trigger neuronal death process 99 …”
Section: The Neural Underpinnings Of Terminal Luciditymentioning
confidence: 99%
“…Close interactions between serotonin projections and memory engram cells. I created this figure for my last manuscript 4 . Here, I revised it by excluding the optogenetic tools on the figure and adding memory engram nuclei of prefrontal cortex (PFC), olfactory bulbus (OB), and nucleus accumbens (NAcc) to emphasize how serotonin fluctuations can easily affect the excitability state of memory engram neurons.…”
Section: The Neural Underpinnings Of Terminal Luciditymentioning
confidence: 99%
“…106 Because tryptophan is a key amino acid for serotonin production, this model is characterized by decreased serotonin production. At this stage, an instantaneous increase of serotonin level by an artificial stimulation, such as optogenetic 107 in other words, the hippocampus retains only the entry circuit of the memory, not the complete information.…”
Section: The Future Of Terminal Lucidity Researchmentioning
confidence: 99%
“…Because tryptophan is a key amino acid for serotonin production, this model is characterized by decreased serotonin production. At this stage, an instantaneous increase of serotonin level by an artificial stimulation, such as optogenetic 107 or pharmacologic, or increase of neural excitability apart from serotonin by a mediator heavily implicated to be increased in elders, such as CRF, can produce an instantaneous episode of lucidity. It was clear that a striking increase in serotonin levels is observed near death when lucid episodes have been commonly documented.…”
Section: The Future Of Terminal Lucidity Researchmentioning
confidence: 99%